2014
DOI: 10.1007/s00345-014-1370-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the PI-RADS scoring system for mpMRI of the prostate: a whole-mount step-section analysis

Abstract: The PI-RADS scoring system showed good diagnostic accuracy: Only PI-RADS 4 and 5 showed high-grade PCa. However, it seems necessary to revise the PI-RADS scoring system concerning DCE in the transitional zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 22 publications
4
49
0
2
Order By: Relevance
“…Although the numbers are small in each subcategory and therefore a powerful statistical calculation is not possible, as the overall PI-RADS score increased the probability of diagnosing prostate cancer and discovering a clinically significant cancer got higher in our series. Junker et al (19) evaluated PI-RADS for classifying mp-MRI findings using wholemount step-section slides as the reference standard. When all single modality scores were combined, a substantially high discriminative ability of prostate cancer detection (AUC, 0.97; 95% CI, 0.95-0.99) was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Although the numbers are small in each subcategory and therefore a powerful statistical calculation is not possible, as the overall PI-RADS score increased the probability of diagnosing prostate cancer and discovering a clinically significant cancer got higher in our series. Junker et al (19) evaluated PI-RADS for classifying mp-MRI findings using wholemount step-section slides as the reference standard. When all single modality scores were combined, a substantially high discriminative ability of prostate cancer detection (AUC, 0.97; 95% CI, 0.95-0.99) was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…It has resulted in high cancer detection rates of >60% in correlation with the findings on mpMRI and has good prediction of tumour aggressiveness [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it shows a good inter-reader agreement [9] . Especially lesions classified as PI-RADS 4 and 5 harbor a high portion of high-grade PCa [7] .…”
mentioning
confidence: 99%
“…Several studies revealed that PI-RADS appears to have a reliable diagnostic accuracy and correlation with tumor aggressiveness [6][7][8] . Furthermore, it shows a good inter-reader agreement [9] .…”
mentioning
confidence: 99%